Propriedades elétricas de cadeias de poliacetileno fluoretadas - Abreu, Leonardo Martins de (2015)
Using Hartree-Fock (HF) and the second-order Møller-Plesset perturbation theory (MP2) methods with the 6-31G(d) basis set, we have investigated the chain length dependence of the dipole moment, linear polarizability, first and second hyperpolarizabilities of fluorinated polyacetylene chains (PFHA). Such properties were calculated using converged geometries obtained at the HF/6-31G(d) e MP2/6-31G(d) levels theory. The converged geometric parameters were obtained from equilibrium geometry of the oligomer with 40 carbon atoms. Our results show that the dipole moment and the first hyperpolarizability grow initially and exhibit a saturation pattern with the size of chain. In opposition, the linear polarizability and second hyperpolarizability present an increase with increasing chain length. It is found that the effects of electron correlation have an important role on the equilibrium geometry and on the electric properties. For the first hyperpolarizability, in particular, the asymptotic value including the electron correlation effects is 17 times larger than the uncorrelated one. These calculations were performed using the GAUSSIAN03, GAUSSIAN09 and Finito.f programs.